2009
DOI: 10.1055/s-0028-1112127
|View full text |Cite
|
Sign up to set email alerts
|

Reasons and Outcomes of Olanzapine Dose Adjustments in the Outpatient Treatment of Schizophrenia

Abstract: These results indicate that psychiatrists tend to modify olanzapine dose according to treatment response. Dose increases seem to be associated with a better response to treatment and not with a worsening of side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Our finding that global illness severity as measured by the CGI-S was the factor most strongly related to antipsychotic dose increase is similar to that found by Suarez et al (2009) and Lipkovich et al (2008) where increasing dose was associated with baseline CGI and PANSS respectively (Lipkovich et al, 2005; Suarez et al, 2009) In addition, both previous studies also demonstrated that a change in illness severity was related to dose increase, a result replicated here. Global illness severity at the time of dosing displayed a stronger association with dose increase compared with change in symptomatology in this study, again similar to the findings of Lipkovich et al (2008) but contrasting with those of Suarez et al (2009) where the relationship with both variables had a similar magnitude.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that global illness severity as measured by the CGI-S was the factor most strongly related to antipsychotic dose increase is similar to that found by Suarez et al (2009) and Lipkovich et al (2008) where increasing dose was associated with baseline CGI and PANSS respectively (Lipkovich et al, 2005; Suarez et al, 2009) In addition, both previous studies also demonstrated that a change in illness severity was related to dose increase, a result replicated here. Global illness severity at the time of dosing displayed a stronger association with dose increase compared with change in symptomatology in this study, again similar to the findings of Lipkovich et al (2008) but contrasting with those of Suarez et al (2009) where the relationship with both variables had a similar magnitude.…”
Section: Discussionsupporting
confidence: 91%
“…Global illness severity at the time of dosing displayed a stronger association with dose increase compared with change in symptomatology in this study, again similar to the findings of Lipkovich et al (2008) but contrasting with those of Suarez et al (2009) where the relationship with both variables had a similar magnitude. Taken together, these results indicate that the level of symptoms and function during the current evaluation is the most important predictor of dose increase, and has stronger effects than changes in the severity of symptoms from previous visits.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, although clinical response cannot be definitively determined based on dosing patterns, these patterns may also be generally reflective of treatment response in some cases. Research in other therapeutic areas has shown that stable dosing of a therapy may be indicative of satisfactory effectiveness, whereas dose escalation may be suggestive of suboptimal treatment response 25 . Thus, given the number of patients receiving treatment and the costs potentially associated with dosing changes (whether reflective of suboptimal treatment response or other factors), real-world dosing patterns and the potential economic and clinical implications represented by these dosing patterns may be an important consideration when characterizing the value of anti-TNF therapy in IBD.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have observed a decrease in weight gain, or weight loss, in patients switching from standard olanzapine tablets (SOT) to orally disintegrating olanzapine (ODO) tablets. In some study, patients treated with ODO experienced a similar mean change in Body Mass Index (BMI) and weight from baseline, to those patients treated with SOT (Karagianis et al, 2009;Suarez et al, 2009). When orally dispersible tablet (ODT) is placed in the mouth, the dosage form disintegrates instantaneously or within a few minutes releasing the drug, which dissolves or disperses in the saliva.…”
mentioning
confidence: 99%